The Influence of Intellectual Intelligence, Emotional Intelligence, and Spiritual Intelligence on Employee Performance with Intervening Variable Job Satisfaction CV. Kirana Bahari.: Pengaruh Kecerdasan Intelektual, Kecerdasan Emosional, Dan Kecerdasan Spiritual Terhadap Prestasi Kerja Karyawan Dengan Kepuasan Kerja Variabel Intervening CV. Kirana Bahari. - Yuda, Faiz Wachida; Sumartik, Sumartik (Indonesian Journal of Innovation Studies, 2021)
This study aims to determine Intellectual Intelligence, Emotional Intelligence, and Spiritual Intelligence on Employee Work Performance with Job Satisfaction Intervening Variable CV. Kirana Bahari. This research is a type of quantitative research with hypothesis testing. The sample used in this study were 50 employees of CV. Kirana Bahari. The analytical tool used in this research is partial least square (PLS). The term PLS specifically means the calculation of the optimal least square fit of the correlation or variance matrix. The primary data in this study were obtained from a questionnaire whose measurement was using a Likert scale which was tested for validity and reliability. The results of this study prove that intellectual intelligence affects job satisfaction, emotional intelligence affects job satisfaction, spiritual intelligence affects job satisfaction, intellectual intelligence affects work performance, emotional intelligence affects work performance, spiritual intelligence affects job performance, job satisfaction affects job performance. work performance, intellectual intelligence affects job performance mediated by job satisfaction, emotional intelligence affects job performance mediated by job satisfaction, emotional intelligence affects job performance mediated by job satisfaction.